Impact of COVID-19 on the Construction Sector of Nepal - Khanal, Nirajan; Singh, Sujan Kumar; Dhungel, Sujan; Wagley, Sulok (AMC Indian Journal of Civil Engineering, 2020)
The construction industry is an inseparable part of the national economy which thrives through the utilization of technical and non-technical resources. Since the COVID-19 outbreak hit Nepal, it has been a really difficult task for the construction sector to initiate a new project or to continue it at a normal pace. Most of the major projects have been affected, and the result is the increase in the project duration and costs. The availability of resources due to disruption of the supply chain is the prime setback the construction industry has dealt with. Additionally, the cut off in labor forces, and the nationwide lockdown clearly exacerbates the situation of this industry. During this unprecedented time, every sector needs monetary assistance from the central and provincial governments, and the construction sector is no exception. However, the lack of rigid policies and monetary guidance seem to add further hardships in coping up with the economic challenges of the present time.